Evaluation of salivary levels of the enzyme alkalin phosphate (Alp)during orthodontic treatment in leveling and aligning stage - عاقل مي; فادي خليل; باسمة يوسف (Latakia University Journal -Medical Sciences Series, 2023)
The trend towards using saliva as a substitute for blood in diagnosing many cases in dentistry has recently increased. Interest in enzymes and the search for a relationship between enzyme levels and treatments has also increased. Aim : To evaluate the levels of acalyanar phosphate in saliva treated patients with fixed orthodontic appliances during the stage of aligning and leveling the teeth. Materials and Methods: The study sample included 9 patients attending the Orthodontics Department who needed treatment with a fixed orthodontic device. A sample of saliva was taken through a syringe before work, after installing the device, and after other appointments, and the saliva was calibrated within the spectronanometer. Results: There was an increase in the enzyme level after 7 days of work, and after 14 days, this increase was statistically significant. Conclusions:use the alkalinase titration in saliva as an indicator.